Management of radiation therapy-induced mucositis in head and neck cancer patients. Part II: supportive treatments - Wei Cheong Ngeow; Wen Lin Chai; Rosnah Binti Zain (Frontiers Media S.A., 2011)
Oropharyngeal mucositis is the acute inflammatory and ulcerative reaction of the oral mucosa following radiation therapy to the head and neck region. It is such a common problem that nearly all head and neck cancer patients develop some degree of mucositis. This complication is usually transient in nature but it also represents an important clinical problem as it is a painful, debilitating, dose-dependent side effect for which there is no widely acceptable prophylaxis or effective treatment. As several authoritative groups have recently either undertaken systematic reviews or issued guidelines on the management of mucositis, it is the aim of this review instead, to provide an overview of all the remedies and pharmaceutical agents available, as well as highlighting to researchers the gaps that need to be filled.